Anchoring Analysis and Simulation of Molecular Dynamics of Dayak Onion Plant Compounds (Eleutherine bulbosa (Mill.) URB.) As an Antibacterial Candidate for Methicillin Resistant Staphylococcus aureus - Pratamaa, Yuga; Rina Herowati; Nuraini Harmastuti; Andri Prasetiyo (PT FORMOSA CENDEKIA GLOBAL, 2024)
MRSA infection that is growing and limited treatment is evidence that the handling and treatment of the disease is still inadequate so that appropriate drugs are needed as antibacterial against MRSA, the development of natural products, one of which is the dayak onion plant (Eleutherine bulbosa) which has the potential as antibacterial can be done with computational methods, one of which is molecular tethering, molecular dynamics and ADMET prediction. This study aims to predict the ability of natural compounds from dayak onions as antibacterial MRSA. Tethering and molecular dynamics are performed using AutoDock 4.2 and Yasara Dynamic software. The results showed that compounds with the greatest antibacterial potential were eleucanainones with binding energy of -11.91kcal / mol. The results of molecular tethering are then continued with molecular dynamics simulations. The results of molecular dynamics simulations show that the compound has a Root Mean Square Deviation (RMSD) value that is close to the native ligand. Conclusion: Dayak onion compounds (Eleutherine bulbosa) have potential as antibacterial MRSA